The Evolution of Civil Liability Insurance in Health Care System - Korytkowska, Daria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The insurance of civil liability are one of the insurance which characterized one of the fastest evolution in the insurance market. Their success is associated especially with the technical development which took place in XIX and XX century. Because of the changes taking in all civilized countries, many institutions and people whose work is fraught with a big risk looks for the instruments protecting their business. One of the possibility is civil liability insurance.At the Polish insurance market one of the biggest evolution had taken a medical civil liability insurance because of the contact with the most valuable goods as health and life. Their history are very short but full of experience. The functioning insurance in mandatory shape just from 1998 till 2014 many changes over. First they obliged a non public medical entities to have this kind of insurance and then expand it on almost every medical facility.